RANCANG BANGUN SISTEM SELEKSI DUTA GENRE (GENERASI BERENCANA) KAB. ASAHAN MENGGUNAKAN METODE SAW - Adinda Mutiara Putri; Herman Saputra; Sri Rezki Maulina Azmi (LPPM Universitas Abdurrab, 2026)
The Generation Planning Ambassador (GenRe) selection is an activity aimed at shaping youth as agents of change in disseminating information on family life planning, reproductive health, and the prevention of early marriage. The GenRe Ambassador selection process involves several assessment criteria that must be considered to determine the best participants. In the assessment process, there were 20 participants who were assessed based on several aspects determined by the selection committee. Therefore, a system is needed that can assist in processing participant assessment data in a structured manner. This study aims to apply the Simple Additive Weighting (SAW) method and build a web-based Decision Support System to assist in the processing and calculation of participant scores in the selection of the Asahan Regency GenRe Ambassador. This system uses five assessment criteria, namely public speaking, work programs during the contract period, attitude and personality, appearance and dress code, and insight and knowledge about the GenRe program. The SAW method is implemented through a process of normalization, weighting, and ranking to generate preference scores for each participant. The results of the study showed that the system built was able to automatically process data from 20 participants, perform SAW method calculations, and produce rankings of male and female participants based on 5 assessment criteria.